Elements for teaching game theory - Malaspina Jurado, Uldarico (Pro Mathematica, 2003)
This article is a lecture accepted for presentation and publication in the proceedings of the 2nd International Conference .on the Teaching of Mathematics, held in Crete on July 2002. Some elements to have in mind for the teaching of Game Theory are given, using the author's teaching experience that relies on the viewpoint that encourages the formal development of mathematical concepts after proposing students problems related with these concepts and after stimulating and analyzing their intuitive approaches to the solution of these problems.